Comb Drive Designs with Minimized Levitation - del Corro, Pablo Guillermo (2016)
This paper presents two capacitive comb drive designs for electrostatic actuation of MEMS with the aim to eliminate the levitation effect often observed in such systems. By placing a shield over the comb drive fingers, it is possible to balance the electric field and suppress vertical forces while maintaining the desired lateral motion. By optimizing the comb geometry, we demonstrate that our approach is able to reduce the levitation by an order of magnitude and unwanted coupling of motion from out-of-plane to in-plane by a factor of 7 compared with standard comb architectures fabricated using PolyMUMPs technology, without the need of alternating comb finger polarities or additional control electrodes. Levitation was reduced to 160 nm, for 3.6 μm lateral displacement at a driving voltage of 80 V. [2016-0156]